Trends and Prospects of Founding Start-Up-Unicorns - A. A. Ivanov; E. Yu. Kulakova; G. M. Magomedova (Вестник Российского экономического университета имени Г. В. Плеханова, 2022)
The article studies the most evident examples of fast growing business from start-ups to companies – unicorns, analyzes causes of their quick success and shows key trends of future start-ups. The authors identify trends of realizing business start-ups of future companies – unicorns, among which technological start-ups, fintech start-ups, start-ups in the field of transport, EdTech, medical start-ups, e-commerce. The authors review the most successful companies-unicorns of the new decade of the 21st century. They analyze different lines in business development from electronic on-line platforms for designing on-line games, education services, estimating the efficiency of ad campaigns and marketing analysis to production of grapheme nano-tubes with higher electro-conductivity and strength. The article identifies vectors of companies – unicorn evolution in view of demand for digital products (services, applications) on the part of internet- space market and information technologies, as well as needs of new technology and innovation market, where the major trend is development of unique materials (production). The role of entrepreneurship of new formation (for B2C market) is demonstrated in order to raise comfort, accessibility and ergonomic characteristics of products/services and at the same time to increase their basic functionality for convenience and relative simplicity for users. The article gives examples of home companies – unicorns that grew up from start-ups, whose capitalization exceeds $1bn. The authors study the most popular markets, where a considerable number of companies – unicorns are located and show statistics of successful start-ups of 2020–2021. Start-up trends and requirements to them aimed at attaining the status of successful company with high capitalization were characterized.